Optimalisasi Media Sosial Sebagai Sarana Promosi Potensi Desa Wonorejo, Kecamatan Pagerwojo, Kabupaten Tulungagung - Muttaqin, Mukhammad Zainul; Siti Anisa Rahmi; Nadim Rifki; Violita Juan Swastika Suparman; Nabilla Eka Indriyani; Annie Nur Choiriah; Fifi Aurielly Sepzinda Priyanka Putri (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Wonorejo Village, located in Pagerwojo District, Tulungagung Regency, has a wealth of local potential, from traditional arts to MSME products such as banana chips and rempeyek. However, the use of social media as a promotional tool is still limited and individuals have not yet integrated it into an organized village promotion system. The purpose of this study was to determine how the use of social media helps promote village potential and to develop sustainable and successful optimization methods. A descriptive qualitative approach was used through observation, interviews, and documentation of MSME actors and the village community. The results showed that two main obstacles in managing social media-based promotions were a lack of digital literacy and limited human resources. To address these issues, an official Instagram account for Wonorejo Village was created to share the village's potential with others, and a digital map of MSMEs was created through Google Maps to facilitate information and expand market reach. It is hoped that this optimization will improve village branding, boost the local economy, and provide greater visibility to the potential of Wonorejo Village to the general public.